Interaction site for the inhibition of tarantula Jingzhaotoxin-XI on voltage-gated potassium channel Kv2.1. (15th December 2016) - Tao, Huai; Chen, Xia; Deng, Meichun; Xiao, Yucheng; Wu, Yuanyuan; Liu, Zhonghua; Zhou, Sainan; He, Yingchun; Liang, Songping
Abstract: Jingzhaotoxin-XI (JZTX-XI) is a 34-residue peptide from the Chinese tarantula Chilobrachys jingzhao venom that potently inhibits both voltage-gated sodium channel Nav1.5 and voltage-gated potassium channel Kv2.1. In the present study, we further showed that JZTX-XI blocked Kv2.1 currents with the IC50 value of 0.39 ± 0.06 μM. JZTX-XI significantly shifted the current-voltage ( I–V ) curves and normalized conductance-voltage ( G–V ) curves of Kv2.1 channel to more depolarized voltages. Ala-scanning mutagenesis analyses demonstrated that mutants I273A, F274A, and E277A reduced toxin binding affinity by 10-, 16-, and 18-fold, respectively, suggesting that three common residues (I273, F274, E277) in the Kv2.1 S3b segment contribute to the formation of JZTX-XI receptor site, and the acidic residue Glu at the position 277 in Kv2.1 is the most important residue for JZTX-XI sensitivity. A single replacement of E277 with Asp(D) increased toxin inhibitory activity. These results establish that JZTX-XI inhibits Kv2.1 activation by trapping the voltage sensor in the rested state through a similar mechanism to that of HaTx1, but these two toxins have small differences in the most crucial molecular determinant. Furthermore, the in-depth investigation of the subtle differences in molecular determinants may be useful for increasing our understanding of the molecular details regarding toxin-channel interactions. Highlights: JZTX-XI inhibited Kv2.1 activation in a voltage-dependent manner. Three common residues (I273, F274, E277) in the Kv2.1 S3b segment contributed to the formation of JZTX-XI receptor site. Acidic residue Glu at the position 277 in Kv2.1 was the most important residue for JZTX-XI sensitivity. JZTX-XI inhibited Kv2.1 activation through a similar mechanism to that of gating modifier HaTx1. JZTX-XI and HaTx1 have small differences in the most crucial molecular determinant.